Planning for scarcity: Developing a hospital ventilator allocation policy for Covid-19. (June 2022) - Ferrell, Emily; Drabiak, Katherine; Alfano-Torres, Mary; Ahmed, Salman; Ali, Azzat; Bjornstad, Brad; Dietrick, John; Foley, Mary M; Garcia-Gonzalez, Alex; Robb, Shannon; Ross, Douglas
Objective: To develop an ethically, legally, and clinically appropriate ventilator allocation policy for AdventHealth Tampa and AdventHealth Carrollwood in Tampa, Florida, which could be enacted swiftly during the Covid-19 pandemic. Methods: During Spring 2020, a subcommittee of the Medical Ethics Committee established consensus on the fundamental principles of the policy, then built on existing ethical, legal, and clinical guidance. Results: The plan was finalized in May 2020. The plan triages patients based on exclusion criteria (imminent mortality), prognosis and expected benefit of ventilation (using the Sequential Organ Failure Assessment), and change in prognosis over time. Decisions are made by committee in order to minimize moral distress among individual patient care providers. Conclusions: Due to international concerns about healthcare resource shortages during the Covid-19 pandemic, hospitals need allocation policies informed by the crisis standard of care, the hospital's ethical duty to plan for an emergency, and federal civil rights laws Policy Implications: This type of policy can serve as a model for other institutions to develop crisis standards of care resource allocation policies, which are a necessary component of disaster planning.